Somatotype of elite cuban paddlers - Aladro Gonzalvo, Arián Ramón (2007)
Some physical characteristics are related to maximum sport performance, which has resulted in what has been denominated the morphological prototype.  Knowing about this concept is of great relevance for physical activity professionals.  Consequently, the purpose of this research was to give evidence as to whether the somatotypes of elite Cuban paddlers are related to international studies done in Spain (Esparza, 1993), Canada (Carter, 1999), Australia (Ackland et al, 2000), Argentina (Lentini et al, 2002), and the United States (Vaccaro et al, 2000).  A total of 30 athletes were evaluated including 9 female kayakers and 21 male canoeists and kayakers. This study shows the significant heterogeneity found in this population based on the behavior of the somatotypes when contrasting the groups.  Compared to the other reference studies, the endomorphic component proved to be the differentiating factor in this research.  The foregoing allowed us to conclude that actions should be taken to modify this component in a way that Cuban athletes are closer to the anthropometric profile exhibited by international elite teams.